Plasma levels of an N‐terminal tau fragment predict core AD and neurodegenerative biomarkers in autosomal dominant Alzheimer's disease: Findings from DIAN. (20th December 2022) - Schultz, Stephanie A.; Liu, Lei; Ostaszewski, Beth; Fitzpatrick, Colleen D; Xiong, Chengjie; Fagan, Anne M.; Noble, James M; Rosa‐Neto, Pedro; Farlow, Martin R.; Schofield, Peter W.; Morris, John C.; Perrin, Richard J.; et al.
Abstract: Background: Blood based biomarkers that predict cognitive decline and Alzheimer's disease (AD) pathology have the potential to accelerate AD therapeutic development and improve clinical care. Prior work suggests that plasma biomarkers of tau pathology (particularly post‐translational modifications of tau) may be highly useful in diagnosis and risk stratification for AD‐related neurodegeneration and cognitive decline. Levels of tau species lacking truncation of the N‐terminal region, particularly plasma and cerebrospinal fluid (CSF) levels of N‐terminal tau fragment 1 (NT1), have previously been shown to predict cognitive decline, neurodegeneration, and tau pathology in preclinical and symptomatic late‐onset AD. Here we examined plasma NT1 as a possible predictor of cognitive, clinical, pathologic, and neurodegenerative trajectories in autosomal dominant AD (ADAD) using data from the Dominantly Inherited Alzheimer Network Observational Study (DIAN‐Obs). Methods: Associations between plasma NT1 levels and Mini‐Mental State Exam (MMSE), Clinical Dementia Rating SumBox® (CDR‐SB), hippocampal volume (HV), estimated years to symptom onset (EYO), Pittsburgh‐Compound‐B PET, and CSF Aβ42, and p‐tau181 were assessed using linear regression (150 pathogenic variant carriers, 81 non‐carriers; mean[SD] carrier age = 40.1 [10.4] years and EYO = ‐5.4 [10.4]). Plasma NT1 was measured using the Quanterix HD‐X platform. PET, MRI, clinical, and biofluid measures were derived using previously described procedures in DIAN‐Obs. Results: Cross‐sectional plasma NT1 levels in ADAD carriers were significantly associated with MMSE, CDR‐SB, HV, and p‐tau181 even after adjusting for EYO (Table 1; Figure 1). NT1 levels statistically diverged between carriers and non‐carriers 6.8 years before estimated symptom onset (Figure 2). In contrast, plasma NT1 levels were not significantly correlated with measures of β‐amyloid pathology after adjusting for EYO. Conclusion: Plasma NT1 levels mirrored changes in clinical, cognitive, and neurodegenerative measures in ADAD, particularly in late asymptomatic and early symptomatic phases of disease. NT1 levels correlated with CSF measures of tau pathology, but NT1 levels were not strongly associated with CSF or PET measures of β‐amyloid pathology, unlike some previously‐studied plasma tau measures. Together with previous supportive findings in preclinical and symptomatic sporadic AD, these results suggest that plasma NT1 may be a useful biomarker of AD‐related tau pathology and neurodegeneration across a broad spectrum of disease.